ANALISIS PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM (KMS) PADA PT. HUMALA GIAT MANDIRI - Nur Anisah Rangkuti; Evy Nurmiati (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
This study discusses the concept of knowledgemanagement and also its application at PT. Humala isindependent. Knowledge management seeks to increaseuseful knowledge in an organization. Qualitativedescriptive method is a research method that the authoruses in this study. Knowledge Management is dividedinto two theories, namely resource based view theory(RBV) and knowledge based view theory (KBV). In thedelivery service company, knowledge management isapplied in the form of increasing resources and utilizingexisting information technology. The purpose of thisresearch is to analyze the application of knowledgemanagement at PT. Independent Active Humala. Theresults obtained in this study are PT. Humala GiatMandiri has implemented knowledge management well.